The EFFECTIVENESS OF ORGANIZATIONAL COMMUNICATION ON DECISION MAKING - Thaci, Hashim; Tambunan, Toman Sony; Aritonang, Bintang Ernawati (Lembaga Riset dan Pengembangan Sumatera Utara, 2024)
This research aims to find out the level of effectiveness of organizational communication to decision making in the Government of North Sumatra Provincial. This type of research is quantitative descriptive where the number of samples as many as 20 people that determined by purposive sampling. The instruments used in this study are organizational communication instruments and decision-making instruments that consist of 10 questions and declared valid and reliable. The instrument used used the Likert scale with 4 options to avoid indecisive answers from the sample. The data obtained is primary and secondary data analyzed based on statistical test provisions such as instrument feasibility tests, hypothesis requirements tests and hypothesis tests. The results showed that the level of effectiveness of organizational communication to decision making in the Government of North Sumatra Provincial is more than 60% which means it is effective enough to contribute to decision making by the leadership.